2023
DOI: 10.3390/molecules28062726
|View full text |Cite
|
Sign up to set email alerts
|

Towards the Sustainable Exploitation of Salt-Tolerant Plants: Nutritional Characterisation, Phenolics Composition, and Potential Contaminants Analysis of Salicornia ramosissima and Sarcocornia perennis alpini

Abstract: Increasing soil salinisation represents a serious threat to food security, and therefore the exploitation of high-yielding halophytes, such as Salicornia and Sarcocornia, needs to be considered not merely in arid regions but worldwide. In this study, Salicornia ramosissima and Sarcocornia perennis alpini were evaluated for nutrients, bioactive compounds, antioxidant capacity, and contaminants. Both were shown to be nutritionally relevant, exhibiting notable levels of crude fibre and ash, i.e., 11.26–15.34 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 90 publications
2
13
0
Order By: Relevance
“…. The levels of chlorogenic and p-coumaric acids, rutin and quercetin were lower than those reported for Salicornia ramosissima and S. perennis alpini [19]. The same was observed for chlorogenic acid and quercetin contents in S. alpini when compared to the results of wild S. fruticosa extracts from Spain and Portugal, while its rutin content was higher [36].…”
Section: Hplc-esi-ms Analysismentioning
confidence: 53%
See 4 more Smart Citations
“…. The levels of chlorogenic and p-coumaric acids, rutin and quercetin were lower than those reported for Salicornia ramosissima and S. perennis alpini [19]. The same was observed for chlorogenic acid and quercetin contents in S. alpini when compared to the results of wild S. fruticosa extracts from Spain and Portugal, while its rutin content was higher [36].…”
Section: Hplc-esi-ms Analysismentioning
confidence: 53%
“…The TPC of S. alpini exceeded the levels previously reported in methanolic extracts of S. alpini gathered from different locations across the Iberian Peninsula, which ranged from 3.43 to 3.77 mg GAE/g DW [33]. For the same species collected from Portugal, Lopes et al ( 2023) reported higher values (38.2 mg GAE/g DW) [19]. S. alpini exhibited higher TPC, similar TFC, and lower CTC than wild S. fruticosa [36].…”
Section: Chemical Pro Lementioning
confidence: 58%
See 3 more Smart Citations